Holocene shifts in riverine fine-grained sediment supply to the East China Sea Distal Mud in response to climate change. (October 2014) - Hu, Bangqi; Yang, Zuosheng; Qiao, Shuqing; Zhao, Meixun; Fan, Dejiang; Wang, Houjie; Bi, Naishuang; Li, Jun
Holocene changes in fine-grained sediment supplies to the East China Sea outer shelf were uncovered, through the mineralogical and geochemical analysis of Core B3 in the East China Sea Distal Mud (ECSDM). Based on the lithology, accelerator mass spectrometry (AMS) 14 C dating, and sea-level change, Core B3 can be divided into two major units: transgressive stage (Unit 1: 12.5–6.8 kyr) and highstand stage (Unit 2: 6.8–0 kyr). Significant discrepancy of dolomite/calcite ratio in the fine fractions (<16 µm) of Changjiang (dolomite/calcite = 3:1) and Huanghe (dolomite/calcite = 1:22) sediments was used as a new uniqueness provenance tracer to distinguish these two riverine sources. Both of the dolomite/calcite ratio and rare earth elements fractionation parameters in the fine-grained sediment indicated distinct provenance shifts of Core B3 during the Holocene. Unit 1 of Core 3 (12.5–6.8 kyr) mainly consists of the reworked and resuspension sediments of the East China Sea shelf during the Holocene transgression, while Unit 2 sediments (6.8–0 kyr) are most likely sourced from the Changjiang and Huanghe. Moreover, mixing curves of dolomite/calcite ratio reveal that the ECSDM continuously received the Changjiang sediment since 6.1 kyr with notable fluctuations, whereas the Huanghe sediment supply began in 6.8 kyr but abruptly stopped during 4.2–0.8 kyr and then appeared again since 0.8 kyr. Temporal changes of the Changjiang and Huanghe fine-grained sediment contribution to the ECSDM are closely related to the formation of modern oceanic circulation system since 6.8 kyr (shelf sea-level change), the '4.2 kyr' climate event, and the followed transition to cold and dry climate condition in the northeastern China (global climate change), as well as the artificial shift of lower Huanghe course inad 1128 in the war against invasion of the northern nomadic nation (human activities).